2013
DOI: 10.1002/ijc.28429
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 inhibition sensitizes colorectal cancer to chemoradiotherapy in vitro and in vivo

Abstract: Increased activity of signal transducer and activator of transcription 3 (STAT3) is common in human malignancies, including colorectal cancers (CRCs). We have recently reported that STAT3 gene expression correlates with resistance of CRC cell lines to 5-fluorouracil (5-FU)-based chemoradiotherapy (CT=RT). This is of considerable clinical importance, because a large proportion of rectal cancers are resistant to preoperative multimodal treatment. To test whether STAT3 contributes to CT=RT-resistance, we first co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 51 publications
(123 reference statements)
2
96
0
1
Order By: Relevance
“…Similar observations were made very recently in colorectal cancer cell lines in which treatment with Stattic resulted in significant increased sensitivity toward chemoradiotherapy while phosphorylated STAT3 was not detectable. Off-target effects of Stattic in these experiments were excluded by demonstrating identical effects of shRNA-mediated silencing of STAT3 (Spitzner et al, 2014). These puzzling observations in our and this recently published study might be explained by technical issues, for e.g., by the inability to detect low levels of phosphorylated STAT3 that can still have a physiological role.…”
Section: Discussionmentioning
confidence: 67%
“…Similar observations were made very recently in colorectal cancer cell lines in which treatment with Stattic resulted in significant increased sensitivity toward chemoradiotherapy while phosphorylated STAT3 was not detectable. Off-target effects of Stattic in these experiments were excluded by demonstrating identical effects of shRNA-mediated silencing of STAT3 (Spitzner et al, 2014). These puzzling observations in our and this recently published study might be explained by technical issues, for e.g., by the inability to detect low levels of phosphorylated STAT3 that can still have a physiological role.…”
Section: Discussionmentioning
confidence: 67%
“…Conversely inhibition of STAT3 or blockade of G-CSF signaling represents a novel strategy for CSC-specific therapy for neuroblastoma. Previous studies demonstrated the role of STAT3 in IL-6 mediated drug resistance in neuroblastoma (35) and showed STAT3 inhibition sensitizes colorectal cancer and nasopharyngeal carcinoma to both radiation and chemotherapy (36, 37). …”
Section: Discussionmentioning
confidence: 99%
“…Transfections with synthetic small interfering RNA (siRNA) duplexes were performed as previously described (16,17). Briefly, for cellular viability assays, cells were reverse transfected with siRNAs (Qiagen, Hilden, Germany; Dharmacon/Thermo Fisher Scientific, Schwerte, Germany) using RNAiMAX (Invitrogen) or HiPerFect (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (9,17). Briefly, 20 μg of whole cell protein lysate was loaded and resolved on an 8% or 10% Bis-Tris polyacrylamide gel.…”
Section: Methodsmentioning
confidence: 99%